2004
DOI: 10.1002/pbc.20244
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis: A treatment related toxicity in childhood acute lymphoblastic leukemia (ALL)—experiences from trial ALL‐BFM 95

Abstract: Symptomatic ON is a rare event in patients treated with BFM-type chemotherapy with an overall 5-year cumulative incidence of 1.8%. The age group >/=10 years, and particularly adolescents >/=15 years have a significantly higher risk of developing ON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
126
6
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(150 citation statements)
references
References 17 publications
12
126
6
6
Order By: Relevance
“…51,52 When analyzing the different treatment components, the following conclusions can be drawn from a BFM point of view:…”
Section: Discussionmentioning
confidence: 99%
“…51,52 When analyzing the different treatment components, the following conclusions can be drawn from a BFM point of view:…”
Section: Discussionmentioning
confidence: 99%
“…Another controversial point of discussion concerns the type of Ojala and co-workers have reported a cure rate with restitutio ad integrum in approximately 30% of patients, 9 while other multi-center studies have shown that approximately 22-24% of symptomatic patients have undergone at least one orthopedic surgery. 15,23 Currently, in severe and rapidly progressive osteonecrosis, a surgical approach is commonly accepted, associated with no weight bearing and physical exercises. In patients with osteonecrosis, smaller lesions and fewer symptoms, the therapeutic approach is generally more conservative, essentially based on the absolute prohibition of loading and active and passive physiotherapy in open kinetic chain.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, a dexamethasone dose ranging from 10 to 14 mg/m 2 is usually used [2,15,28]. In regard to the safety of corticosteroids, it has to be considered that corticosteroid treatment, especially in children older than 10 years, increases the risk of aseptic osteonecrosis [6,20,28]. Furthermore, laboratory studies suggest steroids may interfere with response to chemotherapy in osterosarcoma cell lines, but this has not been shown in vivo [9].…”
Section: Corticosteroidsmentioning
confidence: 99%